Das Verb in Mäsqan - Voigt, Rainer (Aethiopica, 2006)
Proceeding from a review of W. Leslau's work on Mäsqan some special cases of the verbal classes are reconsidered. E.g., the rare class qǝyä ‘(a)wait’ is explained as a four-radical verb containing two weak radicals r and *laryngeal. In the same way, verbs of the D-stem, which are characterized by an unalterable o, e.g. sommänä ‘to fast’, turn out to be four-radical verbs with w as their second radical. The most remarkable feature is the synchronous depalatalisation, which occurs e.g. in the negative perfect (an-tonna ‘he did not set himself down’) contrasting with the positive perfect (čonna) and in the imperfect contrasting with the jussive. This can be explained diachronically by palatalisation being a feature of the B-stem. Another kind of ‘depalatalisation’ occurs in the 3rd pers. plural forms of the perfect and the 3rd and 2nd pers. plural forms of the imperfect of the verbs III y, e.g. impf. yǝfäǧ ‘he completes’ but 3rd plur. yǝfäddo. This is seen as resulting from a morphological compensatory rule affecting in the plural forms not only the original plural ending -u but also the last root radical (i.e., y).